507. Degree of Concordance of Clostridium difficile Strains in Adults with Community-Associated C. difficile Infection and Infants With C. difficile Colonization. (26th November 2018) - Clayton, Jason A; Cadnum, Jennifer; Senders, Shelly; Donskey, Curtis J; Toltzis, Philip
Abstract: Background: The number of adults afflicted with community-associated Clostridium difficile infection (CA-CDI) has increased dramatically over the past 10 years. Exposure to infants, a population known to be asymptomatically colonized by C. difficile (CD), has been identified as a risk factor for CA-CDI, implying that infants may be a reservoir for adult infection. In the present study, we determined the distribution of CD ribotypes isolated from adults with CA-CDI and compared them to the ribotypes of strains excreted asymptomatically among a cohort of healthy infants from the same geographical location. Methods: Adult samples submitted to a referral university hospital microbiology laboratory as part of routine care were identified as CD+ by commercial PCR and stored at −80°; the subset of samples from patients meeting IDSA criteria for CA-CDI were selected for further analysis. A cohort of healthy infants attending a suburban, demographically diverse pediatric practice 6 miles from the hospital were enrolled at birth and prospectively followed at 2-, 6-, and 12-month well-visits. Stool collected at each infant visit was cultivated for CD using routine techniques. DNA from both sets of organisms was extracted and subjected to fluorescent PCR ribotyping. Amplicons were assigned to specific ribotypes through sequence analysis, using the nomenclature proposed previously (J Clin Microbiol 2015;53:1192). Results: To date, 29 adult samples (collected between August 1, 2016 and January 31, 2018) and 32 infant samples (collected between July 1, 2016 and March 31, 2018) have been ribotyped. Eleven (18%) organisms could not be typed (3 adult; 8 infant). The most representative ribotype identified in the adult CA-CDI samples was F014-020 (54%), with small numbers scattered among six other ribotypes. The most prominent ribotypes in infants were F106 (33%), F010 (17%), and F012 (17%); two (8%) infants were colonized with ribotype F014-020. Except for F014-020, there was no concordance of ribotypes among adult CA-CDI and infant isolates. Conclusion: In this population, a small proportion of asymptomatic infants were colonized by a prominent CA-CDI ribotype in adults, but other ribotypes were unique to each age group. Disclosures: All authors: No reported disclosures.